Identifying Metabolic Inhibitors to Reduce Bacterial Persistence - Mohiuddin, Sayed Golam; Hoang, Thuy; Saba, Adesola; Karki, Prashant; Orman, Mehmet A. (Frontiers in Microbiology, 2020)
Bacterial persisters are rare phenotypic variants that are temporarily tolerant to high concentrations of antibiotics. We have previously discovered that stationary-phase-cell subpopulations exhibiting high redox activities were less capable of producing proteins and resuming growth upon their dilution into fresh media. The redox activities of these cells were maintained by endogenous protein and RNA degradation, resulting in self-inflicted damage that transiently repressed the cellular functions targeted by antibiotics. Here, we showed that pre-treatment of stationary-phase cells with an ATP synthase inhibitor, chlorpromazine hydrochloride (CPZ), significantly reduced stationary-phase-redox activities and protein degradation, and yielded cells that were more susceptible to cell death when exposed to antibiotics in fresh media. Leveraging this knowledge, we developed an assay integrating a degradable fluorescent protein system and a small library, containing FDA-approved drugs and antibiotics, to detect medically relevant drugs that potentially target persister metabolism. We identified a subset of chemical inhibitors, including polymyxin B, poly-l-lysine and phenothiazine anti-psychotic drugs, that were able to reduce the persistence phenotype in Escherichia coli. These chemical inhibitors also reduced Pseudomonas aeruginosa persistence, potentially verifying the existence of similar mechanisms in a medically relevant organism.